A QUALITATIVE STUDY OF MENTAL PERSEVERANCE AND MENTAL CONCENTRATION AMONG ELITE AND SUB-ELITE WRESTLERS - Sudesh Bhardwaj; Nandalal Singh; N. K. Rathee (European Scientific Journal, ESJ, 2014)
Sports itself is a stressor and it demands a high level of resolutions, unflagging eagerness and obstinate persistence from its participants. It is believed that athletes having strong mental hardiness, concentration and optimum skill level do have a dominant hand upon the psychological weaker opponents. In sports, right from the motor acquisition stage to the highest competitive performance level, concentration plays an exceptionally vital role. It is a psycho-physiological process, an intense function of mind which is carried out through cognitive abilities and supplemented by emotional and conational factors. This research is an attempt to examine the dimensions of mental toughness and concentration abilities among wrestlers performing at national and international levels. It also attempts to find the interrelationship between these two parameters. The subjects (N=80) were wrestlers performing at two different levels i.e. national (N=40) and international (N=40). The subjects were asked to complete the Mental Toughness Questionnaire and to work on the Concentration Grid Exercise against time. The data was statistically analyzed. The results indicate that the international level wrestlers possessed significantly higher level of mental toughness as compared to the national level wrestlers. Female wrestlers have been found to possess significantly higher level of concentration abilities. No significant correlation was, however, observed between these two parameters.